Legal Status of MoU Determining The Limits of The Territory Area Between Indonesia and Malaysia - Dwi Ambarina Rita Kadarsih; Putra Kurnia, Mahendra; Hidayatullah, Syukri (Faculty of Law, Mulawarman University, 2020)
The border region is the front territory of the country jurisdiction and posses an important role in the matter of enforcement of national law sovereignty. Sebatik Island owned by two countries, Indonesia and Malaysia. Demarcation of territorial boundaries in Sebatik Island refers to Memorandum of Understanding between the Government of Malaysia and the Government of the Republic of Indonesia regarding Surveys and Demarcation of the Border Line of 1973 which is followed up with the results of a joint Surveys and Demarcation on the island of Borneo poured in the form of an advanced Memorandum of Understanding containing each boundary point which has been agreed upon.From 1973 to 2017 there are 9 (nine) points of Outstanding Boundary Problem (OBP) on Sebatik Island that have not been agreed by both countries. The boundary disputes have led to unclear legal status of Sebatik Island's land border territory within the framework of international treaty law and also led to the uncertainty of the status of the MoU as the legal basis for the determination of state borders between Indonesia and Malaysia on Sebatik Island.This law research questioning two issue. First, what factors make the border region not yet regulated by international agreements on borders. Second, how the legal status of the 1973 Memorandum of Understanding in stipulate the point of demarcation between Indonesia and Malaysia in the perspective of international treaty law. Based on the research, the factor that caused the border area not yet been regulated by a definitive border agreement is the disparity of reference between Indonesia and Malaysia to determining the land boundary in Sebatik Island. Indonesia uses the provisions of 4o 10 'LU degree while Malaysia uses existing pillar references. This dispute involve the overlap of the Sebatik Island border area from both countries. Thus, the legal status of the 1973 Memorandum of Understanding has not been binding as law either in national law or as an agreement in international law.